Ageing Transgender People’s Experiences of Health and Health Provision - Wood, Kirilee (Curtin University, 2020)
Research regarding ageing (over 50 years) transgender people in Australia is scarce. A qualitative phenomenological approach, using semi-structured interviews, facilitated a contextual exploration of 19 participant's health and healthcare experiences. Collected data was analysed using NVivo software and Braun and Clarke’s (2006) six-step guidelines for thematic analysis. Findings showed ageing transgender people will benefit from broader ranging data collection that includes population specific estimates and determinants for good health (systematic, psycho-social, economic, environmental).